Design and characterization of a new pressurized flat panel photobioreactor for microalgae cultivation and CO2 bio-fixation. (November 2022) - Carone, Michele; Alpe, Davis; Costantino, Valentina; Derossi, Clara; Occhipinti, Andrea; Zanetti, Mariachiara; Riggio, Vincenzo A.
Abstract: Microalgae-based biorefinery processes are gaining particular importance as a biotechnological tool for direct carbon dioxide fixation and production of high-quality biomass and energy feedstock for different industrial markets. However, despite the many technological advances in photobioreactor designs and operations, microalgae cultivation is still limited due to the low yields achieved in open systems and to the high investment and operation costs of closed photobioreactors. In this work, a new alveolar flat panel photobioreactor was designed and characterized with the aim of achieving high microalgae productivities and CO2 bio-fixation rates. Moreover, the energy efficiency of the employed pump-assisted hydraulic circuit was evaluated. The 1.3 cm thick alveolar flat-panels enhance the light utilization, whereas the hydraulic design of the photobioreactor aims to improve the global CO2 gas-liquid mass transfer coefficient (k L aCO 2 ). The mixing time, liquid flow velocity, and k L aCO 2 as well as the uniformity matrix of the artificial lighting source were experimentally calculated. The performance of the system was tested by cultivating the green microalga Acutodesmus obliquus . A volumetric biomass concentration equal to 1.9 g L −1 was achieved after 7 days under controlled indoor cultivation conditions with a CO2 bio-fixation efficiency of 64% of total injected CO2 . The (gross) energy consumption related to substrate handling was estimated to be between 27 and 46 Wh m −3, without any cost associated to CO2 injection and O2 degassing. The data suggest that this pilot-scale cultivation system may constitute a relevant technology in the development of microalgae-based industrial scenario for CO2 mitigation and biomass production. Graphical abstract: Image 1 Highlights: New alveolar flat panel photobioreactor with positive pressure-serpentine circulation. CO2 supply strategy enhancing the global CO2 mass transfer coefficient ( k L aCO 2 ). Low energy demand for liquid culture circulation and mixing. Acutodesmus obliquus mean daily volumetric productivity of 0.21 g L −1 d −1 . CO2 bio-fixation efficiency equal to 64% of total injected CO2 .